2002
DOI: 10.1001/archotol.128.6.698
|View full text |Cite
|
Sign up to set email alerts
|

Estimating DNA Repair by Sequential Evaluation of Head and Neck Tumor Radiation Sensitivity Using the Comet Assay

Abstract: The comet assay is a promising tool for evaluating radiation sensitivity in individual cells. The rate of DNA repair early after irradiation is consistent with data in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…This discrepancy, at a first glance, can be explained by the fact that the Comet assay does not only detect radiation-induced DNA damages, but also the nicks and gaps that are generated during base excision repair (BER) and nucleotide excision repair (NER) (Asaeda et al, 1998;Collins and Squires, 1986;de With and Greulich, 1995;Kleinau et al, 1997;Olive and Banath, 1993). The repair time measured in our experiments is slow compared with other reports in the literature (Hamilton et al, 2001;Terris et al, 2002), where half-life times of a few minutes to 30 minutes (for SSBs and base damages) have been reported. A possible reason for this is the high UV-A fluences of 960 kJ/m 2 used for the repair study.…”
Section: Resultscontrasting
confidence: 63%
“…This discrepancy, at a first glance, can be explained by the fact that the Comet assay does not only detect radiation-induced DNA damages, but also the nicks and gaps that are generated during base excision repair (BER) and nucleotide excision repair (NER) (Asaeda et al, 1998;Collins and Squires, 1986;de With and Greulich, 1995;Kleinau et al, 1997;Olive and Banath, 1993). The repair time measured in our experiments is slow compared with other reports in the literature (Hamilton et al, 2001;Terris et al, 2002), where half-life times of a few minutes to 30 minutes (for SSBs and base damages) have been reported. A possible reason for this is the high UV-A fluences of 960 kJ/m 2 used for the repair study.…”
Section: Resultscontrasting
confidence: 63%
“…When cells have been extracted from excised human tumours, the alkaline comet assay has successfully identified variations in radiosensitivity in studies of bladder (42), head and neck (14), breast (6) and a range of metastatic tumours (52). These studies further demonstrate how the comet assay could support clinical decision making.…”
Section: Prediction Of Tumour Radiosensitivitymentioning
confidence: 87%
“…With this modification, cell lines of different SF2 values could be separated using doses above 1.0 Gy. Recently, it has been shown that the halflife of repair of human head and neck tumours is about 4 min, showing that the rate of DNA repair following irradiation of human tumours in situ is of a similar order of magnitude to that in vitro (Terris et al, 2002).…”
Section: Discussionmentioning
confidence: 97%